KNOWLEDGE AND ATTITUDES OF NURSING STUDENTS ABOUT AGEING AND FRAIL-ELDERLY CARING AT COLLEGE OF NURSING IN UNIVERSITY OF BAGHDAD - Okab, PHD, Ammar A. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: The issue of an ageing population is a significant one now confronting international healthcare systems. The aging population is associated with a higher probability of experiencing health issues, the aims of this study are to assess the knowledge and attitudes of nursing students about ageing and frail-elderly caring at college of nursing in university of Baghdad. Methods: a cross-sectional descriptive investigation carried out among a cohort of nursing students, study sample included 154 nursing students and was distributed according to department. A researcher used a direct interview sheet to gather the data from January 2023 to March 2023, questionnaire consisted of three major parts, data analysis by utilization of the Statistical Package for the Social Sciences version 26, Qualitative data was presented using frequency, percentage distribution and Chi-square test. Results: Results study show knowledge nursing students about ageing and elderly caring all of their answer were know, attitude nursing students about ageing and elderly caring most of their answer were agree, positive significant relationship between nursing students’ knowledge and attitude about ageing and frail-elderly caring. Conclusion: The nursing student’s assessment of knowledge about ageing and frail-elderly caring and is good in all items, good level of attitude about ageing and frail-elderly caring in all items, age, department and participated in lectures on aging and frail-elderly care, and show high positive significant relationship between nursing students’ attitude about ageing and frail-elderly caring and age, marital status, economic status, and participated in lectures on aging and frail-elderly care.